Matemática aplicada à Economia para o ensino fundamental: uma sequência didática - Laranjeira, Julia Dias Leite (Universidade Federal de São Carlos, 2020)
It has been presented on this work an approach for didactic sequence on mathematical teaching for ninth grade. The key reason for this work is to enhance the student's financial knowledge through basic concepts of microeconomics. The presented didactic sequence is composed of theoretical classes and practical exercises aiming to develop citizens who understand the financial system where they live and to enable them awareness to make responsible decisions.
Mathematics applied to Economy for fundamental education: a teaching sequence
Keywords: Ensino de Matemática; Sequência didática; Matemática financeira; Microeconomia; Mathematical; Financial math; Teaching; Microeconomics; CIENCIAS SOCIAIS APLICADAS::ECONOMIA::ECONOMIA DO BEM-ESTAR SOCIAL::ECONOMIA DO CONSUMIDOR; CIENCIAS HUMANAS::EDUCACAO::ENSINO-APRENDIZAGEM; CIENCIAS HUMANAS::EDUCACAO::FUNDAMENTOS DA EDUCACAO; CIENCIAS EXATAS E DA TERRA::MATEMATICA::MATEMATICA APLICADA